Countries and continents most healthly impacted by Covid-19 as of 08/30/2023 - Mora-Alvarado, Darner (2024)
This study addresses and selects 198 countries globally, through the application of the Covid-19 Health Impact Index (IIS-Covid-19), through the use and development of a model, using the morbidity indicator of confirmed Covid-19 cases/100,000 inhabitants and the mortality indicators of deaths/million inhabitants and the fatality rate of the virus in each country. The results indicate that of the total of 198 nations studied: 67 (33.84%) rated the health impact as “Very Low”, 113 (57.07%) “Low”, 15 (7.58%) “Medium”. ”, 2 (1.01%) “High”, 1 (0.50%) “Very High”. Concluding, Peru followed by Sudan and Croatia were the countries most impacted by the health crisis caused directly by the SARS-CoV-2 virus. In addition to this, the most impacted continent was America with its 35 countries, with 12 countries - including Costa Rica - rated as “Medium” and Peru rated as “Very High” and number one in the world. Europe came in second place, followed by Asia, Africa, and Oceania. On the other hand, specialists' forecasts about the possible collapse of the pandemic in Africa fell, which recommends analyzing possible protective factors such as climate (sunshine hours, temperature and others); longevity and the capacity or expertise acquired in other epidemics such as Ebola, Tuberculosis, Malaria, etc. Finally, the intrinsic weaknesses of this study is the opalescence in the reporting of Covid-19 data, by some countries such as: Nicaragua, North Korea and Turkmenistan. In addition, the change in the definition of deaths due to or with Covid-19.